Study on the Heat of Hydration and Strength Development of Cast-In-Situ Foamed Concrete - Wenhui Zhao; Qian Su; Feng Han; Wubin Wang (Advances in Materials Science and Engineering)
This study aims to investigate the relationship between the heat of hydration and the strength development of cast-in-situ foamed concrete. First, indoor model tests are conducted to determine the effects of the casting density and the fly ash content on the hydration heat of foamed concrete in semiadiabatic conditions. Second, compression tests are carried out to evaluate the development of the compressive strength with the curing time under standard curing conditions and temperature matched curing conditions. Third, the hydration heat development of the foamed concrete is tested in four projects. The results showed that the peak temperature, the maximum temperature change rate, and the maximum temperature difference increased with the increase in the casting density at different positions in the foamed concrete. For the same casting density of the foamed concrete, the peak temperature, the maximum temperature change rate, and the maximum temperature difference decreased with the increase in the fly ash content. For the foamed concrete without the admixture, the early strength was significantly higher under temperature matched curing conditions than under standard curing conditions, but the temperature matched curing conditions had a clear inhibitory effect on the strength of the foamed concrete. The strengths during the early stage and the later stage were both improved under temperature matched curing conditions after adding the fly ash, and the greater the fly ash content, the larger the effect. The maximum temperature increments were higher in the indoor model test than in the field tests for the same casting density. Reasonable cooling measures and the addition of fly ash decreased the maximum temperature increments and increased the corresponding casting times.